2019
DOI: 10.1101/626325
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Potent, specific MEPicides for treatment of zoonotic staphylococci

Abstract: 24Coagulase-positive staphylococci, which frequently colonize the mucosal surfaces of 25 animals, also cause a spectrum of opportunistic infections including skin and soft tissue 26 infections, urinary tract infections, pneumonia, and bacteremia. However, recent 27 45 robustly inhibit DXR in zoonotic staphylococci, and further, DXR represents a 46 promising, druggable target for future development. 3 47 48 Author Summary 49 The proliferation of microbial pathogens resistant to the current pool of antibiotic… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 75 publications
0
8
0
Order By: Relevance
“…We have recently employed lipophilic prodrugging strategies to increase the efficacy of broad-spectrum antimicrobial phosphonate antibiotics. Notably, POM ester modification of a phosphonate isoprenoid biosynthesis inhibitor (ERJ) increases antistaphyloccal activity by 200-and 500-fold for S. schleiferi and S. pseudintermedius, respectively (27). Similar dramatic potency gains are observed for the same class of compounds against Mycobacterium tuberculosis, Yersinia pestis, Franciscella novicida, and the malaria parasite, Plasmodium falciparum (16,(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 91%
See 4 more Smart Citations
“…We have recently employed lipophilic prodrugging strategies to increase the efficacy of broad-spectrum antimicrobial phosphonate antibiotics. Notably, POM ester modification of a phosphonate isoprenoid biosynthesis inhibitor (ERJ) increases antistaphyloccal activity by 200-and 500-fold for S. schleiferi and S. pseudintermedius, respectively (27). Similar dramatic potency gains are observed for the same class of compounds against Mycobacterium tuberculosis, Yersinia pestis, Franciscella novicida, and the malaria parasite, Plasmodium falciparum (16,(28)(29)(30)(31).…”
Section: Introductionmentioning
confidence: 91%
“…In our previous study, we identified phosphonate antibiotics with activity against zoonotic staphylococci (S. schleiferi and S. pseudintermedius) (27). Lipophilic carboxy ester prodrug modification of these phosphonates dramatically increases antistaphylococcal potency, presumably through increased cellular penetration (Fig.…”
Section: Selection Of Prodrug-resistant Staphylococcimentioning
confidence: 99%
See 3 more Smart Citations